Oligothiophene-ring-strapped perylene bisimides: functionalizable coaxial donor-acceptor macrocycles - Dnyaneshwar Veer, Sairam; Chandrakant Wakchaure, Vivek; Asokan, Kiran; Dixit, Ruchi; Goswami, Tanmay; Saha, Ramchandra; Gonnade, Rajesh; Ghosh, Hirendra N.; Santhosh Babu, Sukumaran (Angewandte Chemie-International Edition, 2023)
Aesthetic designs from nature enable new knowledge to be gained and, at the same time, inspire scientific models. In this context, multicomponent macrocycles embody the advantage of precisely positioning the structural units to achieve efficient communication between them. However, the construction of a functionalizable macrocycle for ultrafast charge separation and stabilization has not been attempted. Herein, we report the synthesis, crystal structure, and transient absorption of a new functionalizable macrocycle consisting of an oligothiophene-ring-strapped perylene bisimide. Transient absorption results point to a sequential improvement in charge separation and stabilization from the macrocycle to the corresponding linear dimer and 2D polymer due to the unique design. Our macrocycle design with a supportive spatial arrangement of the donor and acceptor units will inspire the development of more complex synthetic systems with exciting electron-transfer and charge-separation features.
Keywords: Charge Separation; Donor-Acceptor Systems; Electron Transfer; Macrocycles; Perylene Bisimides